2005
DOI: 10.1016/j.pain.2005.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Illness burden mediates the relationship between pain and illicit drug use in persons living with HIV

Abstract: We investigated predictive and concurrent relationships among reported pain, HIV/AIDS illness burden, and substance use history in 2,267 participants in the longitudinal HIV Cost and Services Utilization Study (HCSUS). Substance use history was classified as screening positive for current illicit drug use (N = 253), past drug use (N = 617), and non-user (N = 1397) at baseline. To control for demographic correlates, age, sex and socioeconomic status (SES) were included as predictors. Covariance structure models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
3
28
1
Order By: Relevance
“…Previously, we found that patients with problematic drug use history experienced greater HIV/AIDS illness burden, which in turn predicted greater pain (Tsao et al 2005). Preliminary analyses for the current study revealed that whereas illness burden was related to pain-specific use of opioids in problem drug-users, illness burden was not related to aberrant analgesic use in either the problem or non-problem group.…”
Section: Discussionmentioning
confidence: 38%
See 3 more Smart Citations
“…Previously, we found that patients with problematic drug use history experienced greater HIV/AIDS illness burden, which in turn predicted greater pain (Tsao et al 2005). Preliminary analyses for the current study revealed that whereas illness burden was related to pain-specific use of opioids in problem drug-users, illness burden was not related to aberrant analgesic use in either the problem or non-problem group.…”
Section: Discussionmentioning
confidence: 38%
“…Existing studies have not examined the use of opiates specifically for pain in HIV patients, taking into account previous substance abuse. In light of our prior findings that HIV patients with problem drug use history reported increased pain compared to non-problem users (Tsao et al 2005), it is reasonable to expect that problem drug users would be more likely to evidence increased use of opiates specifically for pain than the non-problem group.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Pain in HIV seropositive persons is exacerbated when there is a coexisting psychological disorder [22,47,52,57], particularly depression [22,32,33]. Injection drug use (IDU) [15,23,37,60], as well as use of other illicit drugs (not just IDU) have also been associated with increased pain in HIV [58]. Efforts to identify which patients are more vulnerable to pain as well as depression and substance use, have indicated some common clinical and sociodemographic characteristics.…”
Section: Introductionmentioning
confidence: 99%